Instrumentation for Ionized Space Environments: New High Time Resolution Instrumental Modes of Mutual Impedance Experiments. Issue 2 (10th February 2023) - Bucciantini, L.; Henri, P.; Dazzi, P.; Wattieaux, G.; Lavorenti, F.; Vallières, X.; Brochot, J. Y.; Colin, F.; Katrougkalou, M. C.; Vengeons, G.; Lecas, T.; Le Duff, O.
Abstract: Mutual impedance experiments are in situ plasma diagnostic techniques for the identification of the plasma density and the electron temperature. Different versions of mutual impedance instruments were included in past and present space missions (e.g., Rosetta, BepiColombo, JUICE and Comet Interceptor). New versions are currently being devised to fit the strong mass, volume and power constraints on nanosatellite platforms for future multi‐point space missions. In this study, our goal is to define and validate two new instrumental modes (i.e., chirp and multi‐spectral modes) to improve the time resolution of the experiment with respect to typical mutual impedance instrumental modes (i.e., frequency sweep). Higher time resolution measurements are expected to simplify the integration of mutual impedance experiments onboard nanosatellite platforms by facilitating antenna sharing between different experiments. The investigation is performed both (a) numerically, using a 1D‐1V electrostatic full kinetic Vlasov‐Poisson model and, (b) experimentally, with laboratory tests using a vacuum chamber and a plasma source. From a plasma diagnostic point of view, we find that both the chirp and multi‐spectral modes provide measurements identical to the (reference) frequency sweep mode. From an instrumental point of view, multi‐spectral measurements are faster than frequency sweep measurements but they require larger amounts of onboard computing resources (i.e., larger power consumption). Chirp measurements, instead, outperform frequency sweep measurements both in terms of measurement duration (20 times faster) and onboard processor usage (20% less). Key Points: New mutual impedance instrumental modes (chirp and multi‐spectral) for higher time resolution measurements are defined, tested and validated The time resolution of mutual impedance measurements is improved by 20 times and the required onboard computing resources are reduced by 20% New fast mutual impedance instrumental procedures are tested and validated using 1D‐1V Vlasov‐Poisson simulations and plasma chamber tests